A User-Centric Approach for Secured eDocument Transmission: Digital Signing Practical Issues and the eCert Solution. Issue 4 (2011) - Chen-Wilson, Lisha; Gilbert, Lester; Wills, Gary B; Gravell, Andrew M; Argles, David
No abstract available